2020
DOI: 10.1021/jacs.0c01475
|View full text |Cite
|
Sign up to set email alerts
|

General C(sp2)–C(sp3) Cross-Electrophile Coupling Reactions Enabled by Overcharge Protection of Homogeneous Electrocatalysts

Abstract: Cross-electrophile coupling (XEC) of alkyl and aryl halides promoted by electrochemistry represents an attractive alternative to conventional methods that require stoichiometric quantities of high-energy reductants. Most importantly, electroreduction can readily exceed the reducing potentials of chemical reductants to activate catalysts with improved reactivities and selectivities over conventional systems. This work details the mechanistically-driven development of an electrochemical methodology for XEC that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
92
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(93 citation statements)
references
References 82 publications
1
92
0
Order By: Relevance
“…c) Hansen's electrochemical coupling in acetonitrile [67] . d) Sevov's electrochemical coupling conditions [70] . *Current density (J) calculated from the RVC electrode reported dimensions and the approximate surface area of the RVC of 100 PPI, 66 cm 2 /cm 3 [53] …”
Section: C‐centered Radicalsmentioning
confidence: 99%
“…c) Hansen's electrochemical coupling in acetonitrile [67] . d) Sevov's electrochemical coupling conditions [70] . *Current density (J) calculated from the RVC electrode reported dimensions and the approximate surface area of the RVC of 100 PPI, 66 cm 2 /cm 3 [53] …”
Section: C‐centered Radicalsmentioning
confidence: 99%
“…Reductive dehalogenation is a classic transformation in electrosynthesis [113] that includes stereoselective examples using cobalt catalysis [99,100]. The principle is relevant for transition metal-catalyzed reductive cross-electrophile couplings [114][115][116], and an enantioselective coupling of alkenyl and benzyl halides using a chiral Ni catalyst was demonstrated by Reisman and co-workers under electrochemical conditions [117]. Electrochemical catalyst activation and turnover granted C(sp 2 )-C(sp 3 ) bond formation without the need for sensitive organometallic reagents or metal powder reductants, and products bearing allyl stereocenters were obtained under mild conditions.…”
Section: Cross-electrophile Couplingsmentioning
confidence: 99%
“…A recent advance in cross-electrophile coupling was reported by Sevov et al (Scheme 5). 41 Using catalyst C1, they identified that a major issue in this class of coupling was overreduction of the ligand, resulting in a much less catalytically active nickel species. This overreduction occurred when the current flowing into the reaction exceeded the rate of catalyst turnover and resulted in a higher effective voltage, or overcharge in the cell.…”
Section: Short Review Synthesismentioning
confidence: 99%